2014
DOI: 10.1186/1478-4491-12-9
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative examination of the health workforce needs during climate change disaster response in Pacific Island Countries

Abstract: BackgroundThere is a growing body of evidence that the impacts of climate change are affecting population health negatively. The Pacific region is particularly vulnerable to climate change; a strong health-care system is required to respond during times of disaster. This paper examines the capacity of the health sector in Pacific Island Countries to adapt to changing disaster response needs, in terms of: (i) health workforce governance, management, policy and involvement; (ii) health-care capacity and skills; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Although there is mounting emphasis in the literature on the adaptive capacity of health care institutions and systems, recent studies have suggested that the individual adaptive capacity of workers at the forefront of health care delivery shows increasing importance to organisational effectiveness in coping with contingencies and changed situations in large‐scale health care emergencies (Rumsey et al . ). The findings of this study offer needed insight into strategies to empower the adaptive capacity of frontline emergency nurses in response to public health events.…”
Section: Discussionmentioning
confidence: 97%
“…Although there is mounting emphasis in the literature on the adaptive capacity of health care institutions and systems, recent studies have suggested that the individual adaptive capacity of workers at the forefront of health care delivery shows increasing importance to organisational effectiveness in coping with contingencies and changed situations in large‐scale health care emergencies (Rumsey et al . ). The findings of this study offer needed insight into strategies to empower the adaptive capacity of frontline emergency nurses in response to public health events.…”
Section: Discussionmentioning
confidence: 97%
“…1 The health impact of climate change is a concern for public health. 2 Extreme events weather are known to contribute to an increase in morbidity and mortality, particularly in vulnerable groups(eg, the elderly, children, and people with chronic diseases). 3,4 From 1999 to 2009, 7233 heat-related deaths occurred in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many Pacific Island countries face a shortage of trained health staff mixed with high staff turnover rates challenging health adaptation and disaster risk management. 36 A national core team dedicated to climate change and health issues may exist, albeit usually within a broader environmental health portfolio. An overload of information (for example, separate assessments for climate change and health, population health, development, and climate change adaptation) and reporting (for example, large numbers of global and national frameworks with many indicators) 37 can lead to "assessment fatigue" among health care workers and technical working groups.…”
Section: Health Adaptation In Pacific Island Countriesmentioning
confidence: 99%